Rhabdomyolysis-Induced Acute Renal Failure Following Fenofibrate Therapy: A Case Report and Literature Review - Danis, Ramazan (Hindawi Publishing Corporation, 2010)
Fenofibrate, a fibric acid derivative, is used to treat diabetic dyslipidemia, hypertriglyceridemia, and combined hyperlipidemia, administered alone or in combination with statins. Rhabdomyolysis is defined as a pathological condition involving skeletal muscle cell damage leading to the release of toxic intracellular material into circulation. Its major causes include muscle compression or overexertion; trauma; ischemia; toxins; cocaine, alcohol, and drug use; metabolic disorders; infections. However, rhabdomyolysis associated with fenofibrate is extremely rare. Herein we report a 45-year-old female patient who was referred to our department because of generalized muscle pain, fatigue, weakness, and oliguria over the preceding 3 weeks. On the basis of the pathogenesis and clinical and laboratory examinations, a diagnosis of acute renal failure secondary to fenofibrate-induced rhabdomyolysis was made. Weekly followups for patients who are administered fenofibrate are the most important way to prevent possible complications.